Protokol SPIKES Sebagai Model Komunikasi Kesehatan dalam Penyampaian Informasi Klinis Kepada Pasien di Praktek Kedokteran Gigi - Hafib Adifaizal; Arief Budiman; Mohamad Yusup Nurjaman; Ike Junita Triwardhani (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Health communication plays a crucial role in dental practice, particularly in conveying sensitive clinical information or bad news. Barriers to communication can increase patient anxiety, decrease adherence to therapy, and impact the quality of healthcare services. The SPIKES protocol presents a six-stage, systematic and empathetic communication model for conveying clinical information. This study aims to analyze the implementation of the SPIKES protocol as a health communication model in dental practice. The study used a systematic literature review method with data sources from the Scopus, PubMed, and Web of Science databases for the period 2020–2025. Article selection was carried out using the PRISMA approach based on inclusion and exclusion criteria. The results of the study indicate that the implementation of the SPIKES protocol can improve the clarity of information delivery, strengthen the relationship between healthcare professionals and patients, and reduce patient anxiety. In addition, the empathetic approach in SPIKES contributes to increased patient satisfaction and adherence to treatment plans. In conclusion, the implementation of the SPIKES protocol can support the improvement of the quality of clinical communication in dental practice through the delivery of targeted, humanistic, and patient-centered information.